3-(3-bromophenyl)-1-(4-methoxyphenyl)-prop-2-en-1-one - Patil, P. S.; Rosli, Mohd Mustaqim; Fun, Hoong-Kun; Razak, Ibrahim Abdul; Puranik, Vedavati G.; Dharmaprakash, S. M. (Acta Crystallographica Section E-Structure Reports Online, 2006)
In the title compound, C16H13BrO2, the dihedral angle between the aromatic rings is 41.34 (6)degrees. The molecules (via two C-H center dot center dot center dot O intermolecular interactions) form chains along the a axis that stack into layers parallel to the b axis.